The Floristic Composition of Sacred Groves - a Functional Tool to Analyse the Miniforest Ecosystem - Sukumaran, S.; Rejini Balasingh, G. B.; Kavitha, A.; Raj, A. D. S. (Indian Forester, 2005)
Sacred groves are one of the traditional, informal conservation concepts for preserving bio-diversity. Present study has brought to light 329 plant species from 251 genera belonging to 110 families from 40 sacred groves. Out of the 110 families, 108 belonging to angiosperms and two to gymnosperms. In the floristic composition also, they are very rich with 139 species of trees, 95 shrubs, 79 herbs and 16 Iianas, climbers and twiners. Nearly 88% plants are of dicots, monocots 11.25% and gymnosperms just represent only 0.61 % from the overall record of flora. Of the 329 species enumerated, 54 are listed rare, endemic and threatened. The groves from the Vilavancode Taluk floristic diversity is the richest (37.9%), followed by Kalkulam, Thovalai and Agastheeswaram taluks. The dominant family was Fabaceae with 16 species to its credit recorded from these groves. The phytogeographic analysis of flora showed that the Asiatic element is predominant, followed by Indian and the Endemics. In the critical observation two Keystone and four Flagship species were identified. Creating awareness among local people, educating all those who are associated in the management of the sacred groves and nearby residents are important in their conservation.